A selective and differential medium for Vibrio harveyi. - Harris, L (1996)
A new medium, termed Vibrio harveyi agar, has been developed for the isolation and enumeration of V. harveyi. It is possible to differentiate V. harveyi colonies from the colonies of strains representing 15 other Vibrio species with this medium. This medium has been shown to inhibit the growth of two strains of marine Pseudomonas spp. and two strains of marine Flavobacterium spp. but to allow the growth of Photobacterium strains. Colonies displaying typical V. harveyi morphology were isolated from the larval rearing water of a commercial prawn hatchery with V. harveyi agar as a primary isolation medium and were positively identified, by conventional tests, as V. harveyi. This agar displays great potential as a primary isolation medium and offers significant advantages over thiosulfate-citrate-bile salts-sucrose agar as a medium for differentiating V. harveyi from other marine and estuarine Vibrio species.